On the future of the Public Policy School - Anheier, Helmut K. (Global policy, 2019)
Initially created as schools of public administration to help consolidate and advance the functioning of the expanding nation state, these institutions evolved into public policy or governance schools over time. As they evolved, they encountered many tensions inherent in a triad of “management and administration - policy analysis and academia - policy making and politics”. Each of the triad corners represents a distinct and relatively powerful constituency: academia mostly interested in analytics; public administrators eager to optimise processes; and policy makers looking for actionable answers. For the most part, schools managed to negotiate the tensions inherent in the triad, but they now face a series of new challenges that will require them to change substantially to maintain their relevance. The article discusses the evolution of public policy schools, presents the reasons behind current challenges and offers several recommendations.
First published: 08 October 2018
Gesehen am 29.05.2019